Why journalism's default neglect of temporality is a problem. (October 2021) - Zelizer, Barbie
This article considers the role of temporality in institutional settings, with particular emphasis on the positioning and impact of temporal choices—or their absence—in journalism. It first discusses why temporality is relevant to institutions like journalism and considers its two interrelated dominant manifestations in the news: nowness and firstness. It then addresses temporality in the current US coverage of the Trump administration. Finally, it considers the need for journalism's reset, arguing that the combined effect of nowness and firstness promotes temporality's neglect in the news and prevents the continual updating of the journalistic mindset from occurring.